IDEOLOGY FOUND IN TOBACCO WARNING LABELS IN INDONESIA’S CIGARETTE PACKAGE - ARTHA, ALMIRA FIDELA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Critical Discourse Analysis, ideology, tobacco warning label The number of cigarette consumption in Indonesia increases every year (GATS, 2012). To minimize this number, several efforts have been implemented, such as the use of tobacco warning label. Historically, the first warning label in 1999 is “Merokok dapat menyebabkan kanker, serangan jantung, impotensi dan gangguan kehamilan dan janin” and recently in 2014 it changes into “Peringatan: Merokok membunuhmu”. This changes and different emphasized meaning indicated hidden ideology. This research is designed to analyze both tobacco warning labels using Critical Discourse Analysis. There is one problem of the study in this research, namely: What are the ideologies constructed in tobacco warning labels in Indonesia’s cigarette packages? And the objective of this research is to find out the ideologies constructed in tobacco warning labels in Indonesia’s cigarette package.This research uses a qualitative approach by using content or document analysis. There are two steps in the data collection. First, is to find out the text or utterances of tobacco warning labels in Indonesia’s cigarette package based on government regulation number 81, year 1999. Second, is to find out the utterances of tobacco warning label based on government regulation number 109, year 2012. In analyzing the data, the researcher only uses one process that is analyzing both tobacco warning label utterances using textual analysis and discursive practice.The result of this study shows that both tobacco warning labels have variety of features of text which conveyed different meaning and intention. At the level of textual analysis, both tobacco warning labels show negative image of smoking and it is to ask the smoker to stop smoking. At the level of discursive practice, the aim of the warning labels is not to decrease smoking consumption or forbid smoking, but to increase smoking awareness.In conclusion, both tobacco warning labels have the same ideology. The ideology is to give freedom to society to protect themselves from the harm of smoking by giving education and increasing society’s awareness that is shown slightly in both tobacco warning labels. For further research, the researcher is expected to be able to develop and explore further by using different theory and different subject in order to help the readers to understand more about the theory of CDA.